The Origins of Monsters : Image and Cognition in the First Age of Mechanical Reproduction. - Wengrow, D. (Rostovtzeff lectures., 2013)
It has often been claimed that ""monsters""--Supernatural creatures with bodies composed from multiple species--play a significant part in the thought and imagery of all people from all times. The Origins of Monsters advances an alternative view. Composite figurations are intriguingly rare and isolated in the art of the prehistoric era. Instead it was with the rise of cities, elites, and cosmopolitan trade networks that ""monsters"" became widespread features of visual production in the ancient world. Showing how these fantastic images originated and how they were transmitted, David